Quantum confinement controlled solar hydrogen production from hydrogen sulfide using a highly stable CdS0.5Se0.5/CdSe quantum dot-glass nanosystem - Apte, Sanjay K.; Garaje, Sunil N.; Naik, Sonali D.; Waichal, Rupali P.; Baeg, Jin-Ook; Kale, Bharat B. (Nanoscale, 2014)
We have demonstrated unique CdS0.5Se0.5 and CdSe quantum dot-glass nanosystems with quantum confinement effect. The stable, monodispersed CdS0.5Se0.5 and CdSe quantum dots (QDs) of size 2 to 12 nm have been grown in a germanate glass matrix by a simple melt quench technique at moderate temperature. XRD and Raman studies show formation of hexagonal CdS0.5Se0.5 and CdSe in the glass matrix. The quantum confinement of CdS0.5Se0.5 and CdSe was studied using TEM and UV-Vis spectroscopy. The band gap of the glass nanosystem was tuned from 3.6 to 1.8 eV by controlling the CdS0.5Se0.5 quantum dot size in the glass matrix. It can be further tuned to 1.68 eV using growth of CdSe quantum dots in the glass matrix. Considering the tuneable band gap of the CdS0.5Se0.5 and CdSe quantum dot-glass nanosystem for the visible light absorption, a study of size tuneable photocatalytic activity for hydrogen generation from hydrogen sulfide splitting was performed under visible light irradiation for the first time. The utmost hydrogen evolution, i.e. 8164.53 and 7257.36 mu mol h(-1) g(-1) was obtained for the CdS0.5Se0.5 and CdSe quantum dot-glass nanosystems, respectively. The apparent quantum yield (AQY) was observed to be 26% and 21% for the CdS0.5Se0.5 and CdSe quantum dot-glass nanosystems, respectively. It is noteworthy that the present glass nanosystem as a photocatalyst was found to be very stable as compared to naked powder photocatalysts.